Optimal vein access selection in adrenal vein sampling via upper extremity approach: a retrospective analysis of 325 cases - Furong Zhang; Ni Zhu; Shuhua Zhao; Rui Han; Juan Shi; Wenfeng Luo; Dong Shi; Xumin Xin; Jun Qian (Scientific Reports, 2025)
Abstract In order to provide some references for vein approach selection in adrenal vein sampling (AVS), this retrospective study analyzed 325 cases of primary aldosteronism (PA) patients who underwent AVS via the upper extremity vein approach, comparing the differences in complications and visual analogue scale (VAS) scores through median cubital vein (MCV), basilic vein (BV), and cephalic vein (CV). The results indicated no significant difference in the incidence of venous spasm (right MCV vs. right BV vs. left MCV vs. left BV: 4.2 vs. 5.9 vs. 5.3 vs. 0.0%, p>0.05) and VAS scores between AVS performed using the MCV and the BV. However, the right CV access was associated with a relatively higher incidence of venous spasm (right CV: 20% vs. right MCV: 4.2%, p<0.05) and higher rate of thrombosis formation (right CV: 5.7% vs. right MCV: 0.0%, p<0.05) than right MCV, accompanied by more severe pain. The study suggests that bilateral MCV and BV are both viable options vein access for AVS. When neither the MCV nor the BV on one side is accessible, it may be more prudent to opt for the MCV or BV on the contralateral side rather than the CV.